Understanding inter-industry wage structures in the euro area - Véronique Genre; Karsten Kohn; Daphne Momferatou (Institute for the Study of Labor (IZA), 2009)
This paper focuses on the euro area wage structure and its potential determinants from a sectoral viewpoint. Merging information from the OECD Structural Analysis database with data from the EU Labour Force Survey, we construct a cross-country panel of 22 industries in 8 euro area countries for 1991-2002. Data inspection confirms the existence of a fairly stable inter-industry wage structure that is similar across countries. We then apply panel data techniques to identify factors explaining inter-industry wage differentials in the euro area. Both workforce characteristics (e.g., human capital variables) and firm-related characteristics (e.g., capital intensity, productivity) contribute significantly. However, considerable wage heterogeneity across sectors remains. Idiosyncratic sector and country specifics, reflecting different socio-cultural and institutional backgrounds, appear to bear a major role. While our empirical analysis only uses direct evidence from workforce and firm-related characteristics, we also try to relate the remaining heterogeneity to institutional characteristics, based on related literature.
urn:nbn:de:101:1-20090513115
Keywords: J31; J24; J51; 330; Euro area; inter-industry wage differentials; panel estimation; firm and workforce characteristics; labour market institutions; Sektorale Lohnstruktur; Europäische Wirtschafts- und Währungsunion; Humankapital; Kapitalintensität; Produktivität; Arbeitsmarktflexibilisierung; EU-Staaten